THE EXPRESSIONS OF CORRECTIVE FEEDBACK IN SECOND LANGUAGE CLASSROOM - Sulistyani, Sulistyani (English Teaching Journal, 2014)
This study aims to review the teacherâs expressions which constitute teacherâs corrective feedbacks (CFs) in oral production and examine the ways the teachers expression revealing teacherâs CFs. The data are in the forms of teachers utterances obtained from four research articles. The result shows that teacher expressions whichÂ constitute CFs cover explicit correction, recast, clarification request, metalinguistic, elicitation, and repetition. While the ways which reveal teacherâs CFs are found to be reduction, negation, andÂ expansion. The area to be corrected commonly involves phonological, grammatical, and lexical errors. So, it can be concluded that in a second language classroom instruction, teacherâs CFs expressions lead learners erroneous utterances to be resolved because by saying